Kinetic study on inducibility of polygalacturonases from Aspergillus flavipes FP-500 - Martínez-Trujillo, Aurora; Aranda, Juan S.; Aguilar-Osorio, Guillermo (Electronic Journal of Biotechnology, 2008)
The aim of this work was to describe growth dynamics, substrate depletion and polygalacturonases production by Aspergillus flavipes FP-500 in batch cultures by means of unstructured models. The microorganism was cultivated on several mono- di- and poly- saccharides, and then the culture development modeled with Monod and Leudeking-Piret equations. The kinetic parameters related to the models (µmax, γx/s, α and β) were obtained by minimizing the quadratic residuals function with a simplex algorithm. An accurate description of experimental data was attained with the proposed models. Besides, modeling provided significant kinetic information on microbial degradation of complex substrates, such as the correlation between specific growth rate µmax and production yield α, suggesting that A. flavipes FP-500 polygalacturonases are actually constitutive, but also that there is a certain degree of induciblility in these enzymatic activities.